2003
DOI: 10.4049/jimmunol.170.9.4489
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pathways for NF-κB Regulation Are Associated with Aberrant Macrophage IL-12 Production in Lupus- and Diabetes-Prone Mouse Strains

Abstract: One characteristic of mice prone to a variety of autoimmune diseases is the aberrant regulation of cytokine production by macrophages (Mφ), noted in cells isolated well before the onset of disease. Strikingly, the pattern of IL-12 dysregulation, in particular, is consistent with the nature of the autoimmune disease that will develop in each strain, i.e., elevated in mice prone to Th1-mediated organ-specific disease (nonobese diabetic (NOD) and SJL mice) and reduced in lupus-prone strains (MRL/+ and NZB/W). Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…Most alterations described in mice are consistent with the hypothesis of an increased DC capacity to activate CD4+ and CD8+ T cells [302], such as upregulation of costimulatory molecules, enhanced secretion of cytokines IL-12p70 and TNF-a [303], and downregulation of IDO [304]. An abnormal cytokine response by DC from T1D patients upon antigenic [305] or nonantigenic stimulation was proposed [306] but has not been confirmed by other studies [307].…”
Section: Apcsupporting
confidence: 72%
See 1 more Smart Citation
“…Most alterations described in mice are consistent with the hypothesis of an increased DC capacity to activate CD4+ and CD8+ T cells [302], such as upregulation of costimulatory molecules, enhanced secretion of cytokines IL-12p70 and TNF-a [303], and downregulation of IDO [304]. An abnormal cytokine response by DC from T1D patients upon antigenic [305] or nonantigenic stimulation was proposed [306] but has not been confirmed by other studies [307].…”
Section: Apcsupporting
confidence: 72%
“…DC may therefore indirectly participate to T1D autoimmunity through a reduced efficacy in stimulating Treg, as is also reported in mice [309] and BB rats [310]. This immature phenotype of T1D human DC may result from abnormal activation of the NF-kB pathway [311], consistently with the strong involvement of this transcription factor in the induction of self-tolerance in mice [157,303].…”
Section: Apcmentioning
confidence: 49%
“…There is a selective requirement for the NF-B family member c-Rel in IL-12 p40 gene expression. Alterations in the ratios of NF-B family members (27) may explain a phenomena observed in this study; NO profoundly inhibited IL-12 p40 expression, but other cytokines that are regulated through NF-B, such as IL-1 receptor antagonist (28), were induced normally (data not shown). Activation of NF-B has been well described through MyD88-independent signal transduction pathways (29), which may also explain why all NF-B-regulated genes are not inhibited by NO to the same extent or with the same kinetics as IL-12 p40.…”
Section: Fig 5 No Inhibits Lps-inducible Nf-b Binding To the Il-12 mentioning
confidence: 76%
“…68 It has been shown that the severity of SLE can be diminished in mice and humans through downregulation of many of these HSP90-dependent inflammatory pathways. [69][70][71][72] Our current studies were undertaken to determine if modulation of HSP90 would decrease mesangial cell inflammatory mediator production and lessen renal disease in MRL/lpr lupus mice.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%